Land cover variability and the changes of land cover pattern in landscape units of Hungary - Szilassi, Péter (JOURNAL OF LANDSCAPE ECOLOGY, 2017)
The land cover of Hungary has changed considerably since the 1990s. In addition to areal changes in land cover (growth in forest areas and decline in arable land in Hungary), the size and shape of the individual land cover patches have also changed influencing the ecological, hydrological and erosion processes of the landscape. In order to be able to predict the trends of future land cover changes, we need to be aware of the characteristics (e.g. frequency) of the changes that have taken place in the landscape units since the 1990s. The aims of the present study are 1) to quantify the variability of land cover changes, and 2) to analyze the changes in land cover pattern on the landscape unit scale from 1990 to 2012. When characterizing land cover changeability, we used the number of land cover changes (i.e. frequency) per land cover patch. We described the change in landscape mosaicism by characterizing the development of the average size of the land cover patches in a landscape unit. Frequency of land cover changes was the largest in the landscapes having sandy soils (in the landscape units of Nyírség and the Danube-Tisza Interfluve). It may be due to the fact that sandy soils of poor water retention are affected mostly by aridification, thus, these are areas where the need is the greatest for land use changes and diversification, which would result in smaller Mean Patch Sizes (MPS). Furthermore, since the 1990s, land cover has hardly changed in the landscape units having chernozem soils with good agricultural conditions (e.g. Mezőföld). The Main Patch Size (MPS) of land cover has decreased the most in areas already having mosaic landscape structure, i.e. foothills and the Sand Ridge, while it has changed the least in areas with good soil fertility. The results can be integrated into the Inventory of landscape units in Hungary, a database describing the geographical characteristics of landscape units.